2008
DOI: 10.1111/j.1755-0998.2008.02297.x
|View full text |Cite
|
Sign up to set email alerts
|

Species identification of aphids (Insecta: Hemiptera: Aphididae) through DNA barcodes

Abstract: A 658-bp fragment of mitochondrial DNA from the 5' region of the mitochondrial cytochrome c oxidase 1 (COI) gene has been adopted as the standard DNA barcode region for animal life. In this study, we test its effectiveness in the discrimination of over 300 species of aphids from more than 130 genera. Most (96%) species were well differentiated, and sequence variation within species was low, averaging just 0.2%. Despite the complex life cycles and parthenogenetic reproduction of aphids, DNA barcodes are an effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
236
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(258 citation statements)
references
References 15 publications
20
236
2
Order By: Relevance
“…Reference sequences (GenBank accession numbers given in Fig. 1) for samples from various geographic regions are taken from Foottit et al (2008), Komazaki et al (2010), Valenzuela et al (2007), and additional sequences released with this study (GenBank accession numbers JX438172 to JX438176). Between-sequence distances were calculated using the Kimura twoparameter model and the resultant matrix summarized in a neighbor-joining tree (Fig.…”
Section: Specimens Of Viviparous Females In All Casesmentioning
confidence: 99%
“…Reference sequences (GenBank accession numbers given in Fig. 1) for samples from various geographic regions are taken from Foottit et al (2008), Komazaki et al (2010), Valenzuela et al (2007), and additional sequences released with this study (GenBank accession numbers JX438172 to JX438176). Between-sequence distances were calculated using the Kimura twoparameter model and the resultant matrix summarized in a neighbor-joining tree (Fig.…”
Section: Specimens Of Viviparous Females In All Casesmentioning
confidence: 99%
“…Our study revealed similar average intraspecific pairwise R. padi sample divergence (0.61%), although the range was larger: 0.00-2.49%. Generally, based on the global data set (Foottit et al 2008;Lee et al 2011), the average genetic divergence of COI barcode sequences within aphid species was reported to be 0.05% (range 0.00-1.00%). Such a low values of divergence are explainable by modest numbers of sequences used by the above reported analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Such a low values of divergence are explainable by modest numbers of sequences used by the above reported analyses. Namely, Foottit et al (2008) exploited three, whilst Lee et al (2011) eight sequences of R. padi when compared to 44 used in our study. Out of 20 partial COI sequences of R. nymphaeae, six COI haplotypes were identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guglielmino et al 2014). Such methods have been particularly useful for closely-related species of aphids that are often only slightly differentiated morphologically, with the existence of different morphs causing further complications (Foottit et al 2008;Lagos 2014;Miller et al 2014;Massimino Cocuzza & Cavalieri 2014, 2015Mróz et al 2015;Lee et al 2015). Molecular methods have also been used extensively for studying the phylogeny of higher categories of aphid taxa (Normark 2000;von Dohlen 2002;Zhang & Qiao 2007Ortiz-Rivas & Martínez-Torres 2010;Wieczorek & Kajtoch 2011;Chen et al 2016;Wieczorek et al 2017).…”
Section: Introductionmentioning
confidence: 99%